Penggunaan Permainan Make & Match untuk Peningkatan Keterampilan Sosial Peserta Didik di SMP Negeri 7 Banjarmasin: The Use of Make & Match Games to Improve Students' Social Skills at SMP Negeri 7 Banjarmasin - Amanda Apriliya; Ali Rachman; Hendro Yulius Suryo Putro (ITScience (Information Technology and Science), 2025)
An effective learning process is not only limited to achieving cognitive goals, but must also consider the development of students' social skills. Cooperative learning, combined with educational games such as Make & Match, can contribute to achieving this goal. This game is designed to improve social interaction, cooperation, and communication among students. This quantitative quasi-experimental study used a single-group pre-test/post-test design. This study involved 31 8th-grade E students at SMP Negeri Banjarmasin No. 7. Data were collected using a social skills questionnaire that met validity and reliability requirements. Data analysis was conducted using a paired Student's t-test and calculation of effect size (Cohen's d). The analysis showed a significant difference in students' social skills levels before and after the implementation of the